Pengembangan Multimedia Interaktif Melalui Smart Application Creator pada Mata Pelajaran IPA Kelas V SD Negeri Gunungpring 1 Muntilan - Nindya Retia Safitri (Prosiding University Research Colloquium, 2021)
This study aims to: (1) produce interactive multimedia products through SmartApplication Creator in the 5th-grade science lesson of Gunungpring 1 state elementaryschool, Muntilan. (2) determine the effectiveness of the developed products. The type ofresearch that already done conducted is Research and Development through 10 stapes.The participants in the preliminary field testing involved 5 students. The participants inthe main field testing involved 8 students and operational field testing involved 18students, all test subjects were 5th-grade students of Gunungpring 1 state elementaryschool, Muntilan. The instrument to collect the data were an interview guide, productevaluation sheets, test, and questionnaire. The data were analyzed using qualitative andquantitative methods. The feasibility is also supported by the results of the materialexpert's assessment, score of 4.6 in the “very feasible” category. The results of the mediaexpert's assessment score of 4.5 in the “very feasible” category. The results of theassessment in the initial field trial score of 4.8 in the “very feasible” category. The resultsof the assessment in the main field trial score of 4.9 in the “very feasible” category. Theresults of the assessment on the operational field trials score of 5.0 in the “very feasible”category. This interactive multimedia has a very good effectiveness based on the results ofthe paired sample t-test with a significance level of less than 5% and is shown through anincrease learning outcomes by 27% with an average score of the pre-test being 65,3 andpost-test 89,3. The results show that the developed interactive multimedia has veryfeasible and effectiveness.